2003
DOI: 10.1590/s0104-66322003000400006
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional numerical aerodynamics of a movable block burner

Abstract: Abstract. Computational fluid-dynamics techniques were employed to study the aerodynamics of a movable block swirl burner, developed by the International Flame Research Foundation, IFRF, which is characterized by the ability to adjust continuously and dynamically the intensity of the swirl by means of the simultaneous rotation of eight movable blocks, inserted between eight fixed blocks. Five three-dimensional grids were constructed for the burner, corresponding to five positions of the movable blocks. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The comparison of the velocity distribution in the burner and quarl of the furnace, obtained in the present study, with the results of Fudihara et al, 2003, for the array burner plus quarl, where the mass flow rate boundary condition was applied at the quarl exit, showed analogous results for ξ/ξ m = 0.75 and 1.0. Unlike the previous study, however, no numerical convergence was found for ξ/ξ m = 0.5, probably due to the very unstable flow verified in the combustion chamber, owing to the low swirl intensity.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The comparison of the velocity distribution in the burner and quarl of the furnace, obtained in the present study, with the results of Fudihara et al, 2003, for the array burner plus quarl, where the mass flow rate boundary condition was applied at the quarl exit, showed analogous results for ξ/ξ m = 0.75 and 1.0. Unlike the previous study, however, no numerical convergence was found for ξ/ξ m = 0.5, probably due to the very unstable flow verified in the combustion chamber, owing to the low swirl intensity.…”
Section: Discussionsupporting
confidence: 73%
“…The burner in this study was the same as that analyzed by Fudihara et al, 2003 with eight movable blocks located in between eight fixed blocks. The quarl used corresponded to Nozzle 2 of the experiments performed in the Delft furnace, with a quarl half expansion angle, γ, of 35°.…”
Section: The Furnacementioning
confidence: 99%
See 3 more Smart Citations